Polyphenol and flavonoid content in major Teff [Eragrostis tef (Zuccagni) Trotter] varieties in Amhara Region, Ethiopia. - Chaltu Reta; Minaleshewa Atlabachew; Tihitinna Asmellash; Woldegiorgis Hilluf; Marie Yayinie; Tessera Alemneh Wubieneh (PLoS ONE, 2022)
Teff [Eragrostis tef (Zuccagni) Trotter] is a small-sized cereal grain and an indigenous crop in Ethiopia. The Amhara region is one of the major teff producers regions in the country. However, information on the phenolic content of the region's teff varieties is limited. Seventy-two teff samples were collected from three administrative zones (West Gojjam zone, Awi zone, and East Gojjam zone) of the Amhara region of Ethiopia. The samples' total polyphenol and flavonoid contents were determined using colorimetric methods. The total flavonoid contents expressed as catechin equivalent, CE (i.e., under alkaline conditions) and quercetin equivalent, Q.E (i.e., under the methanolic solution of AlCl3) were found to be in the range of 7.66 ± 0.60-57.36 ± 3.87 mg C.E and 15.45 ± 0.15-113.12 ± 3.09 mg Q.E per 100 g of teff samples, respectively. The corresponding total polyphenol content (TPC), described as gallic acid equivalent (G.A.E.), was in the range of 46.21 ± 1.20-133.32 ± 5.44 mg G.A.E. The results showed that the mean TPC value of the teff samples from the West Gojjam zone was enriched with polyphenol than samples from the Awi zone and East Gojjam. Furthermore, it was noted that the mean TPC and TFC values did not vary significantly between samples of the East Gojjam and Awi zone (p > 0.05). In contrast, a significant difference in mean TPC and TFC-Q.E were noted between the sampling zone of East Gojjam and West Gojjam and between West Gojjam and Awi zones (p < 0.05). These significant variations in TPC and TFC might be due to observable variations in the agroecological zones and the genetic-make-up of the samples. Person correlation indicated a significant positive correlation matrix between the three variables (p = 0.01). The teff samples were trying to be classified based on their geographical origin using hierarchical cluster analysis (HCA) and biplots. Accordingly, the variance explained by component 1 (PC1) is 67.2%, and the variance explained by component 2 (PC2) is 20.0%.